2014
DOI: 10.4067/s0301-732x2014000300017
|View full text |Cite
|
Sign up to set email alerts
|

Aerobe and anaerobe facultative Gram-negative bacteria rod-shaped in the ruminal fluid of dairy cattle fed with different diets containing tropical forages

Abstract: RESUMENLas bacterias Enterobacteriaceae se encuentran naturalmente en los intestinos y ecosistema ruminal y están ampliamente distribuidas. El objetivo de este estudio fue cuantificar Enterobacteriaceae en el líquido ruminal de vacas lecheras y terneras alimentadas con diferentes dietas de forrajes tropicales. Se recolectaron muestras de fluido ruminal de 30 vacas alimentadas con ensilaje de sorgo y concentrado, 32 vacas alimentadas con Brachiaria brizantha, 12 terneras alimentadas con ensilaje de sorgo con co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
1
0
6
Order By: Relevance
“…Bacteria belonging to the genera Proteus spp., Raoultella spp., Citrobacter spp., and Klebsiella spp. were recovered in the ruminal fluid of dairy cattle, rumen samples, and bovine fecal material [30][31][32]; their occurrence in ruminants could be expected because some of these genera, such as Pantoea, Raoultella, and Citrobacter, are reported to be cellulase-producing bacteria [10,33]. Moreover, according to Mao et al [34], in addition to Proteobacteria, Firmicutes is a predominant phylum found in rumen samples of dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria belonging to the genera Proteus spp., Raoultella spp., Citrobacter spp., and Klebsiella spp. were recovered in the ruminal fluid of dairy cattle, rumen samples, and bovine fecal material [30][31][32]; their occurrence in ruminants could be expected because some of these genera, such as Pantoea, Raoultella, and Citrobacter, are reported to be cellulase-producing bacteria [10,33]. Moreover, according to Mao et al [34], in addition to Proteobacteria, Firmicutes is a predominant phylum found in rumen samples of dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Para os animais alimentados com volumoso, a média de unidade formadora de colônia (UFC/ml) e as taxas de positividades não diferiram estatisticamente entre os bovinos de diferentes idades (p>0,05). Diferentemente, em nosso estudo conduzido com bovinos leiteiros da raça Holandesa (Freitas et al 2014), verificou-se que as bezerras apresentaram maior população dessas bactérias no ambiente ruminal, comparando-se com vacas leiteiras adultas que recebiam a mesma fonte de volumoso (silagem de sorgo).…”
Section: Cultivo E Quantificaçãounclassified
“…Essa maior população de bactérias em novilhos alimentados com grãos poderia ser justificada uma vez que esses microrganismos promovem a degradação de carboidratos mais simples (Ostling et al 2006). Bezerras leiterias alimentadas com cana-de-açúcar e ureia apresentaram elevado número dessas bactérias no fluido ruminal, o que foi relacionado com a maior concentração de carboidrato disponível no volumoso, uma vez que nessa gramínea são detectados altos níveis de sacarose, que é facilmente degradada no rúmen (Freitas et al 2014). Krause et al (2003) avaliaram o efeito da dieta sobre a população Enterobacteriaceae e verificaram grandes concentrações ao longo do trato digestório de bovinos.…”
Section: Cultivo E Quantificaçãounclassified
See 2 more Smart Citations